Soluble Interleukin-6 Receptor is a Prognostic Marker for Relapse-Free Survival in Estrogen Receptor-Positive Breast Cancer. (1st October 2013) - Won, Hye Sung; Kim, Young Ae; Lee, Jun Sang; Jeon, Eun Kyoung; An, Ho Jung; Sun, Der Sheng; Ko, Yoon Ho; Kim, Jeong Soo
<x xml:space="preserve">Abstract</x> Considering the protumorigenic roles of interleukin-6 (IL-6) transsignaling, we assessed the serum levels of IL-6, soluble interleukin-6 receptor (sIL-6R), and soluble glycoprotein 130 (sgp130) in 143 patients with breast cancer. Serum levels of IL-6 were elevated with advanced T and N stage. Serum levels of sIL-6R were lower in patients with estrogen receptor-positive cancer. The median values of IL-6 and sgp130 did not differ between patients with recurrence and those without recurrence. However, higher serum levels of sIL-6R at diagnosis were associated with significantly shorter relapse-free survival in patients with estrogen receptor-positive breast cancer.